Kaedah penyelidikan Bahasa Melayu - Nazir, Faridah; Rosli, Nurul Jamilah; Nahar, Nora'Azian (SYFE Management Sdn Bhd, 2020)
This book counts the disclosure of the concept, characteristics, and types of research that can be conducted in Malay. In addition, there is also information on methods of data collection and analysis as well as writing recommendations and research reports. Indirectly, this book develops students' knowledge and skills to implement research projects. The information in this book also provides students with a variety of strategies and techniques that can be used to address research proposals and reports. At the same time, all the discussions in this book are able to highlight some of the realities and general difficulties in conducting various research methods.